On top of the game? The double‐edged sword of incorporating social features into freemium products - Rietveld, Joost; Ploog, Joe N. (Strategic Management Journal, 2022)
Research Summary Freemium products require widespread diffusion for their success. One way to do this is by incorporating social features (e.g., multiplayer functionality, virtual collaboration, ridesharing), which can generate network effects and result in a product becoming a superstar . However, social features can be a double‐edged sword: When demand potential for freemium products is large, social features can significantly boost a product's appeal resulting in more adoption, more usage, and more in‐app purchases; but when demand potential is constrained, network effects might fall short and users may feel they are missing out on key aspects of the product. We test this dynamic on a sample of 9,700 digital games on Steam. Findings contribute to our understanding of network effects, freemium strategies, and superstar products in platform markets. Managerial Summary Freemium has become a popular business model among firms competing on digital platforms. Freemium products require widespread diffusion because most consumers do not pay for premium upgrades. One way to stimulate a product's diffusion is by incorporating social features (e.g., multiplayer functionality, virtual collaboration, ridesharing). Social features can boost a product's appeal resulting in more adoption, more usage, and more in‐app purchases. Our analysis of 9,700 digital PC games on Steam reveals that the efficacy of incorporating social features importantly depends on the number of users on the platform itself. Social features can help freemium products become a superstar when the platform's installed base is large, but they hinder a freemium product's success when the platform's installed base is small.